Measuring spatial accessibility for wheelchair users: A case study in a Chinese campus - Yizhe Huang; Chaobo Shi; Shujie Dong; Shuichao Zhang; Linghui Xu; Guangyue Nian (PLoS ONE, 2025)
Barrier-free campus environment is essential for students and staffs with mobility impairment. However, few studies have empirically examined the spatial accessibility for wheelchair users within the campus. This study aims to investigate the travel characteristics of wheelchair users, so as to better guide the planning and design of barrier-free campus facilities. Thirty students with wheelchair experience were recruited, and their travel characteristics navigating various types of facilities were analyzed. To analyze the effect of explanatory variables on their travel speeds, a decision tree regression method was applied. Based on the empirical results, the existing pedestrian accessibility model was further extended to represent the accessibility of wheelchair users with different travel destinations. Results revealed that the type of barrier-free facility and travel mode (with or without assistance) had the most significant impact on the travel speed for wheelchair users. The average travel speed of assisted wheelchair users was 1.03 m/s, while the speed was 0.67 m/s for wheelchair users without assistance. For unassisted wheelchair users, it was challenging for them to pass through the curb ramps with slopes steeper than 1:5. The visualization results of wheelchair accessibility revealed spatial inequality within the study area, which can be further improved by upgrading existing barrier-free facilities and optimizing the allocation of different destinations.